A problemática trazida pela homologação de sentenças arbitrais estrangeiras anuladas em seu país de origem na segurança jurídica dos contratos internacionais do comercio - Casquel, Diego Garcia Vieira [UNESP] (2014)
With the acceleration of the globalization process, international commercial contracts gain an innovation push, aiming at adapting to such new markets and demands, considering their indispensability in the achievement of these businesses as a tool capable of offering legal certainty. The increasing number of contracts executed in this scenario, in which arbitration stands almost absolute as chosen mechanism for the resolution of disputes, inevitably creates a greater number of initiated arbitration procedures. International treaties, such as the New York Convention, seek to assure the effectiveness to these arbitrations with international nature. However, recognition decisions of foreign arbitral awards set aside in the country in which they were made have been verified, in opposition to the provisions set in the New York Convention and other treaties in this sense, directly affecting the legal certainty of the international commercial contracts, creating a need to rethink legal certainty